«The History of Aḥiqar» as a Pedagogical Instrument in Elephantine and in the Book of Tobit - Díez Herrera, Pablo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2025)
The Story of Aḥiqar is a reference work of wisdom in the Ancient Near East. In this paper it is analyzed as a pedagogical instrument in two realities that respond to different social contexts and different times, but which have as a common denominator the fact of being part of what we can call Yahwism of the Diaspora. We study the profile of the Assyrian sage and his teaching as a model for the training of scribes in the Judahite community of Elephantine, and we contrast it with the presence and influence of this character in the book of Tobit. The result allows us to verify the qualitative leap that has occurred in Yahvist piety of the Diaspora from the Persian to the Hellenistic period.